THE USE OF CARBON AND OXYGEN STABLE ISOTOPES IN THE STUDY OF GLOBAL PALAEOCEANOGRAPHIC CHANGES: EXAMPLES FROM THE CRETACEOUS SEDIMENT ROCKS OF WESTERN GREECE - Karakitsios, V.; Tsikos, H.; Agiadi - Katsiaouni, K.; Dermitzoglou, S.; Chatziharalambous, E. (Bulletin of the Geological Society of Greece, 2006)
In the present paper we examine the use of carbon and oxygen stable isotopes in the study of global palaeoceanographic changes, with special reference to the oceanic anoxic events (OAEs). The analysis of stable isotopes was applied to the examination of Cretaceous sediments from the Ionian and Pindos zones of Western Greece. In the Ionian zone the carbon and oxygen stable isotopes, combined with biostratigraphic data, record the palaeoenvironmental change corresponding to the anoxic events Bonarelli (Cenomanian/Turonian, OAE2) and Paquier (Lower Albian, OAE1b). In the Pindos zone, within the Cretaceous sediments, we observed two organic-carbon-rich levels. According to the biostratigraphic and isotopie analysis, the first level corresponds to an OAE of Santonian age. This local oceanic anoxic event is described for the first time. The second level, Aptian - Albian age, possibly correlates to either the Paquier event (OAE 1b) or the Selli event (OAE 1a), which in Greece were until now known only in the Ionian zone.